Sumoylation influences DNA break repair partly by increasing the solubility of a conserved end resection protein - Sarangi, Prabha; Steinacher, Roland; Altmannova, Veronika; Fu, Qiong; Paull, Tanya T; Krejci, Lumir; Whitby, Matthew C; Zhao, Xiaolan (PLoS genetics, 2015)
Protein modifications regulate both DNA repair levels and pathway choice. How each modification achieves regulatory effects and how different modifications collaborate with each other are important questions to be answered. Here, we show that sumoylation regulates double-strand break repair partly by modifying the end resection factor Sae2. This modification is conserved from yeast to humans, and is induced by DNA damage. We mapped the sumoylation site of Sae2 to a single lysine in its self-association domain. Abolishing Sae2 sumoylation by mutating this lysine to arginine impaired Sae2 function in the processing and repair of multiple types of DNA breaks. We found that Sae2 sumoylation occurs independently of its phosphorylation, and the two modifications act in synergy to increase soluble forms of Sae2. We also provide evidence that sumoylation of the Sae2-binding nuclease, the Mre11-Rad50-Xrs2 complex, further increases end resection. These findings reveal a novel role for sumoylation in DNA repair by regulating the solubility of an end resection factor. They also show that collaboration between different modifications and among multiple substrates leads to a stronger biological effect.
Keywords: Saccharomyces cerevisiae Proteins; Exodeoxyribonucleases; poškození DNA; endodeoxyribonukleasy; exodeoxyribonukleasy; DNA Damage; Endonucleases; fosforylace; Saccharomyces cerevisiae; Phosphorylation; Sumoylation; sumoylace; DNA vazebné proteiny; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; rozpustnost; oprava DNA spojením konců; DNA Repair; oprava DNA; endonukleasy; DNA End-Joining Repair; lidé; Humans; Endodeoxyribonucleases; Saccharomyces cerevisiae - proteiny; DNA-Binding Proteins; Solubility